Improving Early Reading Ability Using Flash Card Media for Class V Mild Mentally Retarded Students at SLB Negeri Merangin - Nelly Nelly; Damri Damri (Edumaspul: Jurnal Pendidikan, 2022)
This reserach improve early reading skills and also to see whether the provision of flash card can be influential or effective in overcoming reading difficulties in mild mentally retarded students at SLBN Merangin. This study uses an experimental approach in the form of a single subject (SSR) using the ABA design. The subject in this study is a child with mild mental retardation. The target behavior in this study was to improve early reading skills. The data analysis technique used is the visual graph technique. The result of this research is that giving intervention using flash card can improve reading ability in mild mentally retarded students at SLBN Merangin. The results of this study are that in the first stage, the baseline (A1) obtained the final percentage of 47%, the intervention stage and the baseline (A2) had obtained the percentage of 100%.